2018
DOI: 10.1021/acs.langmuir.8b01565
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Compatible Surfaces with Phosphorylcholine-Based Polymers for Cardiovascular Medical Devices

Abstract: For the acquisition of blood-compatible materials, various hydrophilic polymers for surface modification have been examined. Among them, polymers with a representative phospholipid polar group, the phosphorylcholine (PC) group, are a successful example. These polymers were designed from inspiration of the cell membrane surface and provide protein adsorption resistance even following contact with plasma. This important property is based on the unique hydration state of water molecules surrounding hydrated polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 128 publications
0
115
0
Order By: Relevance
“…Among various amphiphilic polymers, MPC-based polymers are considered to be optimal due to their high cytocompatibility and high water solubility. [129][130][131] The polymers are composed of an MPC unit and a redox unit, and the EET property is expected to be controlled by various parameters, such as molecular weight, unit composition ratio, and the kind of redox unit (Figure 7a). Actually, redox-active phospholipid polymers, poly(MPC-co-VFc) (pMFc, E = +0.5 V, Figure 7b) [132] and Me 8 -pMFc (E = +0.18 V, Figure 7b) [133] with redox-active ferrocene analogues have been developed.…”
Section: Actual Cases Using Type II Mediatorsmentioning
confidence: 99%
“…Among various amphiphilic polymers, MPC-based polymers are considered to be optimal due to their high cytocompatibility and high water solubility. [129][130][131] The polymers are composed of an MPC unit and a redox unit, and the EET property is expected to be controlled by various parameters, such as molecular weight, unit composition ratio, and the kind of redox unit (Figure 7a). Actually, redox-active phospholipid polymers, poly(MPC-co-VFc) (pMFc, E = +0.5 V, Figure 7b) [132] and Me 8 -pMFc (E = +0.18 V, Figure 7b) [133] with redox-active ferrocene analogues have been developed.…”
Section: Actual Cases Using Type II Mediatorsmentioning
confidence: 99%
“…However, there are reports of imcompatibility of PEG‐based surface modification in vivo. [33] Some papers reported natural antibodies of the IgM isotype directed against PEG in healthy individuals, and experiments performed in rats have demonstrated that a second dose of PEGylated liposomes is rapidly cleared from the blood circulation as a result of antibody recognition. [34] Therefore, the occurrence of antibodies against structures on materials intended for use in contact with blood, either ex vivo or implanted in vivo, is an important situation to be considered when designing new biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ether bond in the PEG chain can easily be attacked by reactive oxygen species generated from leukocytes, which results in its degradation. [33] In fact, the formation of a protein adsorption layer was found within three weeks and thrombus formation was observed within 1 month after implantation, indicating that the PEG coating effect is transient. [35] On the other hand, the MPC polymer is stable against reactive oxygen species since it does not contain ether bond, but carbon–carbon bond.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Yung and Cooper [ 34 ] also found that the incorporation of phosphorylcholine into the polyurethanes could effectively reduce neutrophil adhesion. Typical and efficient synthesis method of MPC was reported by Ishihara et al [ 35 ] and their research team did a lot of works on the polymers containing 2-methacryloyloxyethyl phosphorylcholine (MPC) [ 36 ]. Moreover, they also proved that phosphorylcholine group could effectively reduce protein adsorption [ 37 ].…”
Section: Introductionmentioning
confidence: 99%